Cameroon - Can School Grants and Teacher Incentives be Used to Increase School Access and Improve Quality? - World Bank (World Bank, Washington, DC, 2020)
The Results in Education for All Children (REACH) Trust Fund at the World Bank funded a feasibility study and a pre-pilot of performance-based school grants and teacher incentives among 20 rural primary schools in Cameroon. The purpose was to assess whether these RBF mechanisms could feasibly be used to improve transparency, financial management, and monitoring at the school level, increase community satisfaction, and draw lessons from the implementation of these RBF mechanisms to enable the initiative to be scaled up throughout Cameroon. While it is not possible to draw conclusions about the effect of this RBF program on education access or quality given the short time period and small sample size, this pre-pilot demonstrated that RBF is feasible in rural primary schools in Cameroon and highlighted the importance of several critical preconditions that must be in place for RBF to be effective. These preconditions include a simple and context-appropriate design, clear communication with key stakeholders, effective monitoring tools to assess school and teacher performance, and community involvement.